Sistem Informasi Ketenagakerjaan (Sisnaker): Sisnaker - Pratigina, Dhita; Djuniardi, Dede (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
Ministry of Manpower (Kemnaker) launched an online-based platform, The Employment Information System (Sisnaker). Sisnaker enables all existing information systems in all ministries or agencies and local governments to work together across organizational boundaries. In addition to having implications for the effectiveness and efficiency of existing services, Sisnaker will also improve the integration of planning, implementation, evaluation, and control of labor development in Indonesia as a single national job market. Minister of Manpower (Menaker) M. Hanif Dhakiri considers that the presence of Sisnaker is very important so that the community can get good, excellent and real time services to be able to access all 16 services of the Ministry of Manpower. Starting from job seekers, ministries/agencies, companies, and others.